2018
DOI: 10.2514/1.c034811
|View full text |Cite
|
Sign up to set email alerts
|

Testing of a Hinged Wingtip Device for Gust Loads Alleviation

Abstract: Recent aircraft designs have considered higher aspect ratio wings to reduce induced drag for improved fuel efficiency; however, to remain compliant with airport gate requirements, folding wing-tips have been introduced as a solution to the increased wingspan. Recent numerical studies suggest that a folding wing-tip solution may be incorporated with spring devices to provide an additional gust loads alleviation ability in flight as well. In this work, a series of low-speed steady and dynamic wind tunnel tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 17 publications
(19 reference statements)
4
47
0
Order By: Relevance
“…Consequently, the lift contribution by the wingtip is also reduced, which can lead to a lower peak bending moment along the wing during the gust encounter. This gust load alleviation characteristic was experimentally demonstrated in a previous study [15], in which the effect of folding hinge stiffness was also investigated. It was found that a low hinge stiffness gave a good level of gust load alleviation performance, with results suggesting further gains could be obtained if the responsiveness of the folding action could be improved.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consequently, the lift contribution by the wingtip is also reduced, which can lead to a lower peak bending moment along the wing during the gust encounter. This gust load alleviation characteristic was experimentally demonstrated in a previous study [15], in which the effect of folding hinge stiffness was also investigated. It was found that a low hinge stiffness gave a good level of gust load alleviation performance, with results suggesting further gains could be obtained if the responsiveness of the folding action could be improved.…”
Section: Introductionsupporting
confidence: 58%
“…By utilizing an appropriate hinge geometry, a folding wingtip could function as a passive gust load alleviation device as well. This benefit originates from the geometric relationship between the orientation of the wingtip folding axis and the change in the effective angle of attack of the wingtip as it folds, which is described by [15,16] ∆ = − arctan(tan sin )…”
Section: Introductionmentioning
confidence: 99%
“…By allowing the folding wingtip to rotate freely about the hinge inflight, an additional degree of freedom is introduced to the aeroelastic system of the wing which warrants closer examination to help understand its effect on the dynamic behavior of the overall system. One key observation, already established from previous experimental works 2,6 , is the reduction of peak wing-root bending moment in one-minus-cosine gust conditions. However, very limited test-based dynamic analysis of the folding wingtip concept has been performed.…”
Section: Introductionmentioning
confidence: 72%
“…Mathematical models of a flared folding wingtip device fitted on a large civil aircraft have led to the assessment of the gust load alleviation capabilities (Castrichini et al, 2016) and impact on roll dynamics of the aircraft . Wind tunnel tests also highlighted the loads alleviation potential of the wingtip on a sub-scale model (Cheung, Castrichini, & Cooper, 2017;Cheung, Rezgui, Cooper, & Wilson, 2018. A summary of the findings around the use of folding hinged wingtips (Wilson et al, 2017) was also published as part of the same project.…”
Section: Application To Large Civil Aircraftmentioning
confidence: 99%